Stigma in Practice: Barriers to Health for Fat Women - Lee, Jennifer A.; Pausé, Cat J. (Frontiers in Psychology, 2016)
In this paper, we explore barriers to health for fat people. By shifting the focus from what fat people do or do not do, neoliberal principles are replaced by a focus instead on structural and institutional policies, attitudes, and practices. This includes the impact of stigma on the health treatment and health-seeking behaviour of fat people. For example, we consider the role that provider anti-fat attitudes and confirmation bias play in the failure to provide evidenced-based healthcare to fat patients. This is an autoethnographic paper, which provides the opportunity to read research from the perspective of fat scholars, framed by questions such as: can fat people have health? Is health itself a state of being, a set of behaviours, a commodity, a performance; perhaps the new social contract? As a co-written autoethnographic paper, one aspect of the evidence provided is the recorded experiences of the two fat authors. This includes writing from notes, journals, compiled and repeated experiences with medical professionals, family and the community. Framed by feminist standpoint and supported by literature drawn from Fat Studies, Public Health, Obesity Research, and other interdisciplinary fields, this is a valuable opportunity to present an extended account of fat discrimination and the impact of the stigma fat people face through the medical profession and other sectors of the community, written by fat individuals. The paper concludes by considering the health pathways available to fat people. Special attention is paid to whether Bacon and Aphramor’s Health at Every Size paradigm provides a path to health for fat individuals.